Velocity dispersion and attenuation of acoustic waves in critical mixtures - T. HORNOWSKI; M. ŁABOWSKI (Archives of Acoustics)
Theoretical considerations on critical ultrasonic dispersion and attenuation in binary liquid mixtures based on the mode-coupling approach and frequency-dependent heat capacity are presented. A general expression for the critical amplitude A (T) in terms of the parameter d = (ρc^0_v,x/Tα_p) x (dT_c/dP) is derived. It is shown that for specific values of d one obtains expressions for A (T) equivalent to those of Fixman, Kawasaki, Mistura and Chaban. Moreover, an experimental test has been carried out on the system methanol-n-hexane showing good agreement between our general expression for A (T) and experimental data.